2021
DOI: 10.1038/s41467-021-24774-6
|View full text |Cite
|
Sign up to set email alerts
|

The upstream 5′ splice site remains associated to the transcription machinery during intron synthesis

Abstract: In the earliest step of spliceosome assembly, the two splice sites flanking an intron are brought into proximity by U1 snRNP and U2AF along with other proteins. The mechanism that facilitates this intron looping is poorly understood. Using a CRISPR interference-based approach to halt RNA polymerase II transcription in the middle of introns in human cells, we discovered that the nascent 5′ splice site base pairs with a U1 snRNA that is tethered to RNA polymerase II during intron synthesis. This association func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Secondly, consistent with current co-transcriptional mRNA 3' end processing model (41,42,50), RNAPII pausing and high RNAPII Ser2P density were observed near the intronic PAS for those intronic PCPAed genes upon U1 AMO treatment, while the trend was not apparent for non-PCPAed genes (Figure 3B), indicating that Ser2P and 3' end processing might be uncoupled during the process of transcription termination for these non-PCPAed genes under U1 AMO condition, which adds a layer of complexity to the regulatory mechanism of co-transcriptional mRNA 3' end processing. Third, although our study and previous studies have suggested that the U1 snRNP and RNAPII might have physical interactions (Figure 2C) (23,(30)(31)(32), it remains unclear if this association is direct or indirect, particularly in a cellular context, which may enable us to understand how U1 AMO caused the differential RNAPII activity.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Secondly, consistent with current co-transcriptional mRNA 3' end processing model (41,42,50), RNAPII pausing and high RNAPII Ser2P density were observed near the intronic PAS for those intronic PCPAed genes upon U1 AMO treatment, while the trend was not apparent for non-PCPAed genes (Figure 3B), indicating that Ser2P and 3' end processing might be uncoupled during the process of transcription termination for these non-PCPAed genes under U1 AMO condition, which adds a layer of complexity to the regulatory mechanism of co-transcriptional mRNA 3' end processing. Third, although our study and previous studies have suggested that the U1 snRNP and RNAPII might have physical interactions (Figure 2C) (23,(30)(31)(32), it remains unclear if this association is direct or indirect, particularly in a cellular context, which may enable us to understand how U1 AMO caused the differential RNAPII activity.…”
Section: Discussionmentioning
confidence: 66%
“…Recent studies have shown that U1 snRNP associates with RNA polymerase II (RNAPII) (23,(30)(31)(32); we next investigated if this association is disrupted in U1 AMO treated cells. Using a well-established antibody (8wg16) targeting the CTD (C-terminal domain) of RNAPII, our Co-IP analysis confirmed that RNAPII could interact with U1C and/or U1A in the control HeLa cells (Figure 2C).…”
Section: U1 Amo May Affect U1 Snrnp Structural Integrity In Vivo and ...mentioning
confidence: 99%
“…These recent results highlight the intimate connection between splicing and 3' end processing; through pausing, upstream RNA splicing has more time to complete, promoting overall messenger maturity before polyadenylation and export. Recent studies suggest that messenger maturity is controlled by a checkpoint that involves the upstream splice sites (Leader et al, 2021). Binding of the U1 spliceosome subunit to the 5' splice site (SS) suppresses polyadenylation some distance downstream, a phenomenon termed telescripting (Berg et al, 2012).…”
Section: Pol II Pausing In Terminal Intronsmentioning
confidence: 99%
“…By suppressing the processing of internal fortuitous polyadenylation sites (PAS) located mostly in introns, telescripting prevents premature polyadenylation of partially transcribed genes. The 5' SS and U1 spliceosome subunit remain attached to Pol II while the intron is transcribed (Leader et al, 2021), but are ejected from the RNA as soon as the spliceosome assembles after 3' SS recognition by U2 (Lee and Rio, 2015). The binding and ejection of U1 thus provide a simple mechanism to promote elimination of the terminal intron before activation of the PAS which defines the terminal exon; pausing in this region promotes U2 binding (Mora Gallardo et al, 2019) and subsequent processing.…”
Section: Pol II Pausing In Terminal Intronsmentioning
confidence: 99%
“…Using a CRISPR-based approach to halt RNA polymerase II transcription in the middle of introns, it has been demonstrated that the nascent 5 splice site base pairs with a U1 snRNA that is tethered to RNA polymerase II during intron synthesis [60]. This mechanism relies on the strength of the 5 ss-snU1 RNA and enables the co-transcriptional assembly of the E-complex by ensuring proximity of the U1 snRNP at the 5 ss and the SF1-U2AF complex at the 3 ss.…”
Section: Co-transcriptional Splicing Of Long Introns and Intron Loopingmentioning
confidence: 99%